2016
DOI: 10.1177/0033294116662685
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Exploratory Report of Coping Strategies Among Police Recruits During Academy Training

Abstract: Few longitudinal studies have investigated the use of coping strategies among police recruits. This study investigated perceived life and work stressors, appraisal, and coping over a seven-month police recruit academy training program. Participants were 81 police recruits who completed the Ways of Coping Questionnaire at three time points approximately three months apart. The average age of the recruits was 27.6 years (SD = 5.1, range 20-51). Separate repeated measures analyses of variance were conducted to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
(35 reference statements)
1
4
0
1
Order By: Relevance
“…One study examined the association of mental status of police recruits and periodontal health (29) with other (N = 3) examining the associations of personality and mental health (20,21,31). In other studies coping behaviors of police recruits during training have been examined, suggesting that the training is a potentially stressful environment (32,33), with recruits reporting an increase in alcohol consumption in part to cope with stress (33). However, little remains known about the mental health and symptoms of distress among police recruits.…”
Section: Background Basic Training For Police Officersmentioning
confidence: 99%
“…One study examined the association of mental status of police recruits and periodontal health (29) with other (N = 3) examining the associations of personality and mental health (20,21,31). In other studies coping behaviors of police recruits during training have been examined, suggesting that the training is a potentially stressful environment (32,33), with recruits reporting an increase in alcohol consumption in part to cope with stress (33). However, little remains known about the mental health and symptoms of distress among police recruits.…”
Section: Background Basic Training For Police Officersmentioning
confidence: 99%
“…Coping strategies are often classified as adaptive (positive) or maladaptive (negative). They are also sometimes categorized as emotion focused (attempts to regulate emotional responses), problem focused (attempts to change, alter, or solve issues), and seeking support (Patterson, 2016). At least two studies of officers have found the following strategies to be the most commonly used: active coping, planning, and acceptance (Maran et al., 2015; Salinas & Webb, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scenario-based training has been found to be the most influential and the most remembered training for police recruits (Broomé 2011;Hundersmarck 2009). Many of these training processes involve the use of problem-focused methods aimed at changing or removing the stressor (Patterson 2016;Lazarus and Folkman 1984;VandenBos 2007). For example, defensive tactics such use-of-force are problem-focused methods aimed to eliminate or curb violent behavior from offenders.…”
Section: Difficulties In Copingmentioning
confidence: 99%